Kajian Literatur Review: Riset Akuntansi Keperilakuan - Devinda Ramdani; Ameliya Ameliya; Siti Rodiah (Universitas 45 Surabaya, 2024)
This study examines the evolution of behavioral accounting research over a 17 year period (2007–2023). The main focus of research includes theme classification, research methods, research topics, and number of articles. The approach used is descriptive qualitative, and data is collected through a literature search system or literature review. The results show that the articles were evaluated and taken from journals that have a Sinta index or accreditation of Sinta 2. This can be summarized as follows: (1) Theme Mapping: the topic of Moral Resoning has 9 articles, the topic of Theory of Planned Behavior has 6 articles, the topic of Locus of Control there are 6 articles, the Fraud topic has 6 articles, the Machiavellian topic has 4 articles, the Love of Money topic has 2 articles, (2) Research Method Mapping: the Survey/quiz topic is the most common method with 3 articles, the Theoretical/non-empirical topic is 3 articles that use this method. (3) Research Subject Mapping: Accountant or auditor topic 10 articles, Academic or student topic 9 articles, Unknown subject topic 9 articles, Employee or stakeholder topic 4 articles, There are no articles related to bankers and taxpayers/investors out of 30 reviewed articles. (4) Mapping the Number of Articles: Theory of Planned Behavior (TPB) topic with 72, Locus of Control (LoC) topic with 91, Fraud topic with 70, Machiavellian Nature topic with 13, Love of Money topic with 66 , the topic of Moral Resoning with a total of 92. These findings provide an in-depth picture of the focus, methods, and research subjects in the behavioral accounting domain during the period studied. This information can serve as a basis for identifying trends and future research directions in this area.